Urban Morphological Analysis Framework for Sustainable Malay Town Transition in Response to COVID 19 (International Journal of Built Environment and Sustainability, 2022)
Current approaches applied in the historical analysis on the morphological evolution of early Malay towns primarily focused on describing how cities were formed and transformed without much emphasis on how they can be analysed. Considering cities as urban organisms experiencing rapid growth, achieving a sustainable urban transition would be impossible without understanding the process of initial formation and spatial uniqueness that comprise the Malay town. However, analysing the particular kind of processes requires a comprehensive understanding of each hierarchical level of morphological elements, which, therefore, posed a greater challenge in excerpting Malay town's dynamic and organic growth pattern-development. This study attempt to develop the methodological process of urban morphological analysis framework concerning the Malay town context. With the adoption of the historic-geographical approach as the method of analysis, the study applied two different spatial scales as the basis of the analysis process, that is, plan-units analysis and morphological evolution analysis. The findings unveiled the inherent morphogenesis processes of Malay towns central to the spatial structure of Kota, represent a town that functioned as a territorial base with settlements of Kampung as the archetype of the morphological unit. Through depicting the spatial boundary of Dalam Kota and Luar Kota, the fixation line of the growth process in Malay town can be identified, which is imperative to the functioning system of the town. Accordingly, developing the systematic morphological analysis process aids in providing a clear and responsive strategy for managing the changing process of Malay towns to ensure a sustainable transition for resilient communities and territories
Keywords: Urban Morphological Analysis, Historico-geographical Approach, Malay Town, Morphogenesis Process, Sustainability